PARTISIPASI MASYARAKAT DESA DALAM PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DI DESA BINUANG KECAMATAN SEPAKU KABUPATEN PENAJAM PASER UTARA - Farhanuddin Jamanie (Jurnal Paradigma (JP), 2017)
The research will examine the participation of society in Independent National People Empowerment Program (PNPM Mandiri) in Binuang village Sepaku Sub District, Penajam Paser Utara Regency for the following aspects: people participation in planning the program, the implementation of the program based on the guidelines, the evaluation based on what have been achieved, the socialization based on people concensus. The hindering factors of the program are the lack of human resources, low economic power and lack of socialization.